Heart Fatty Acid Binding Protein for the Diagnosis of Myocardial Ischemia and Infarction. (1st May 2017) - Collinson, Paul O; Hersey, Jennifer; Bray, Rosalind; Gaze, David; Lim, Pitt; Firoozi, Sami; Ntalianis, Argyrios; Boa, Frances; Prasad, Abhiram
Abstract: Objective: To establish the analytical performance of a heart fatty acid binding protein (HFABP) method suitable for routine clinical use and examine its role for the diagnosis of myocardial ischemia and myocardial infarction. Methods: Analyses of HFABP were performed on an Advia 2400 (Siemens Healthcare Diagnostics). Imprecision, limit of detection (LOD), limit of blank (LOB), and linearity were assessed using standard methods. Stability was assessed at 4 °C, −20 °C, and with 3 repeated freeze-thaw cycles. Clinical diagnostic performance was assessed using chest pain in patients, with a final diagnosis according to the universal definition of myocardial infarction with cardiac troponin I (cTnI) measured on the Siemens Advia Centaur (cTnI Ultra method, 99th percentile 50 ng/L, 10% CV 30 ng/L). Ischemia was detected using sampling pre- and postangioplasty. Results: LOD and analytical imprecision exceeded the manufacturer's specification (LOD 1.128 μg/L, 20% CV 1.3 μg/L, 10% CV 2.75 μg/L). Clinical diagnostic efficiency was less than cTnI. Addition of HFABP to cTnI produced a modest increase in diagnostic sensitivity at a cost of significant loss of specificity. Conclusions: Although the test had excellent analytical performance, it did not contribute to the clinical diagnosis of patients with chest pain. HFABP appears to be a marker of myocardial infarction not myocardial ischemia.